2001 Philippines yearbook. (Manila Fookien Times Yearbook Pub., 2000)
Purpose: This book is meant "to portray the development of our nation as well as publish essays about issues that will most certainly concern the Philippines in the 21st century."
Contents: Stories of survival and perseverance. Updated financial and statistical data in CD-ROM. Advertising pages.
Title from cover.
Earlier eds. entered under title: The Fookien Times Philippines yearbook.
Keywords: Philippines -- Periodicals